LuCSD3 enhances salt stress tolerance in flax: genome-wide profiling and functional validation of the SOD gene family - Zhang, Yuan; Wang, Ruinan; Wang, Hengping; Wang, Huiyan (Frontiers in Plant Science, 2025)
Superoxide dismutase (SOD) serves as a critical regulator of plant stress adaptation to salinity, drought, and heavy metal toxicity. Flax (Linum usitatissimum L.), a globally cultivated oilseed and fiber crop, lacks comprehensive genomic characterization of its SOD gene family. Here, we systematically identified 12 LuSOD genes in the flax genome. Phylogenetic reconstruction of SOD homologs across diverse plant species classified these genes into three evolutionarily conserved subgroups: Cu/Zn-SOD (6 LuCSD), Fe-SOD (3 LuFSD), and Mn-SOD (3 LuMSD). Comparative analysis of exon-intron architectures and conserved motifs revealed high structural conservation among LuSOD members within each clade. Promoter cis-element profiling identified predominant associations with phytohormone signaling (abscisic acid, methyl jasmonate) and abiotic stress responses, including hypoxia, drought, and low-temperature adaptation. MicroRNA target prediction identified lus-miR159 as the primary regulatory miRNA interacting with LuSOD genes. Gene ontology (GO) enrichment highlighted LuSOD roles in stress perception, metal ion chelation, and enzymatic reactive oxygen species (ROS) scavenging. Transcriptomic profiling demonstrated ubiquitous high expression of LuSOD genes in leaf tissues. qRT-PCR validation under cold, drought, and salt stresses revealed significant upregulation of nine LuSOD genes, implicating their involvement in antioxidant defense mechanisms. Functional characterization of LuCSD3 in transgenic Arabidopsis confirmed its role in enhancing salt tolerance through ROS homeostasis modulation. This study provides foundational insights into LuSOD-mediated stress resilience, serving as a valuable resource for molecular breeding and functional genomics in flax.